1992
DOI: 10.1093/infdis/166.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis against Wound Infection following Herniorrhaphy or Breast Surgery

Abstract: The effect of perioperative antibiotic prophylaxis on definite wound infections was assessed for 3202 herniorrhaphies or selected breast surgery procedures. Patients were identified preoperatively and monitored for greater than or equal to 4 weeks. Thirty-four percent of patients (1077/3202) received prophylaxis at the discretion of the surgeon; 86 definite wound infections (2.7%) were identified. Prophylaxis recipients were at higher risk for infection, with a higher proportion of mastectomies, longer procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 6 publications
0
32
1
Order By: Relevance
“…Rates of postoperative infections in breast and axillary incisions have ranged from less than 1% of cases to nearly 20%, as shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A meta-analysis by Platt and colleagues [22] from 1993 analyzed data from 2587 surgical breast procedures and found an overall wound infection rate of 3.8% of cases.…”
Section: Wound Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of postoperative infections in breast and axillary incisions have ranged from less than 1% of cases to nearly 20%, as shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A meta-analysis by Platt and colleagues [22] from 1993 analyzed data from 2587 surgical breast procedures and found an overall wound infection rate of 3.8% of cases.…”
Section: Wound Infectionsmentioning
confidence: 99%
“…These studies have yielded disparate results; many have shown that a single dose of a preoperative antibiotic (usually a cephalosporin, administered approximately 30 minutes preoperatively) effectively reduces wound infection rates by 40% or more [8,13,21,22], and the meta-analysis by Platt and colleagues [22] revealed that antibiotic prophylaxis reduced wound infection rates by 38%, despite the selection bias of antibiotics being used predominantly in higher-risk cases. Furthermore, the lowest reported rates of breast wound infections occurred in a phase III study [16] of a long-acting versus a short-acting cephalosporin, revealing greater risk reduction with the former (0.45% versus 0.91%).…”
Section: Wound Infectionsmentioning
confidence: 99%
“…A probable wound infection was Community: all patients examined Aim: to ascertain whether considered to be present if erythema 1 week postoperatively and invited preoperative antibiotic extended at least 2 cm from the for re-examination 3 weeks later prophylaxis would reduce wound in any direction wound infection rates after umbilical and incisional Reference to definition: Sheretz. 33 Conhernia repair sensus paper on the surveillance of SWIs; Glenister et al; 28 Platt and co-workers 124 Grading system: none Anon., 1996, 36 Multicentre prospective study Definition: 1988 CDC Further definition of DSWI given as: cardiac surgical unit. If patient Study Group, Aim: to ascertain the an infection involving tissues of the spaces discharged before postoperative France incidence of deep sternal beneath the subcutaneous tissue.…”
Section: Medline and Healthstarmentioning
confidence: 99%
“…The strategy of no prophylaxis was always associated with both higher costs and a greater number of deaths and surgical site infections than either of the two alternative prophylactic strategies. In fact, the cost attributed to failure to provide prophylaxis may have been underestimated, since we assumed that the risk reduction was similar to that observed in other clean surgical procedures (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed a relative risk of 0.4 for a surgical site infection in patients who received antibiotic prophylaxis compared with those who did not, which corresponds to the highest effectiveness of antibiotic prophylaxis within the range of results from completed placebo-controlled studies in clean surgical procedures other than CABG surgery (18)(19)(20)(21)(22)(23). We used data on the incidence of surgical site infections among patients receiving cefazolin from five surveillance programs in university-affiliated hospitals in Boston (17).…”
Section: Clinical Datamentioning
confidence: 99%